PTU-092 Crohn's disease: strictureplasty and risks for further surgery. (22nd June 2015) - Chan, D; Kumar, D; Mendall, M
Abstract : Introduction: Surgery plays an important role in the treatment of Crohn's disease. Strictureplasty in particular is a practical and attractive treatment for Crohn's disease, conserving bowel length. Only a few large surgical series have been published in the literature. We describe our own experience and factors that determine risk of reoperation or death over a ten year period. Method: All the Crohn's disease strictureplasties for a specialist IBD surgeon at St George's Hospital from 1st January 2005 to 31st December 2014 were identified. Information was collected for weight, height, gender, smoking status as well as their medical and surgical management. Patients whose records were incomplete were contacted for further information. Results: There were a total of 53 cases of strictureplasty, with just under 3, 400 months of follow-up. 22 had concurrent bowel resection. 32 were male. Mean age of diagnosis was 24 years and 10 months. Mean time from diagnosis to first ever surgery was 6 years and 3 months. Mean number of prior surgeries was 1. Total number of further surgery in the follow-up period was 11, with mean time to reoperation 42 months. No patients died during in the follow-up period. 86.54% were non smokers. At the time of surgery 30.25% had a low BMI, 60.45% had a normal BMI and 9.3% had a high BMI. 72.55% were receiving treatment with the immunomodulators: azathioprine, 6-mercaptopurine or methotrexate. Kaplan Meier survival analysis was used to compare those that had strictureplasties and those that had strictureplasty and concurrent bowel resection, with further surgery or death up to 31st December 2014 as the endpoint. Log rank test for trend did not find that there was any significant difference between the two groups and probability of further surgery. Cox regression analysis was used to assess for risk for further surgery: age of diagnosis, number of previous surgeries, time from diagnosis to first ever surgery, treatment with immunomodulators, concurrent bowel resection, sex, BMI and smoking status. Significant risk for further surgery was found in those that had ever smoked (hazard ratio 4.775, p = 0.003) and those patients with a low BMI who had concurrent bowel resection as well as strictureplasty (hazard ratio 6.31, p = 0.002). Importantly previous surgery and age of diagnosis were not a risk factor for recurrent surgery (hazard ratios 1.016 and 1.198 respectively). Conclusion: We review a decade of strictureplasties in the management of Crohn's disease and have identified significant risks for further surgery of smoking and low BMI as well as concurrent bowel resection. We show that strictureplasty remains a viable and attractive management for stricturing Crohn's disease with no deaths resulting from the surgery and a low number of reoperations. Disclosure of interest: None Declared.